Kinetics of air drying of jackfruit and mango pulp and development of mixed leather - Amin, Md Khairul; Islam, Md Ahmadul; Akter, Farzana; Islam, Md Nazrul (Fundamental and Applied Agriculture, 2019)
The study was concerned with the kinetics of dehydration of jackfruit and mango pulp and their use for the development of mixed leather. Kinetics study showed that jackfruit pulp dried faster than mango pulp. The chemical composition of fresh jackfruit and mango pulp showed that moisture, ash, protein, fat, vitamin-C, acidity, pH and total soluble solids content were found 74.23%, 0.86%, 1.55%, 0.60%, 5.04 mg 100g−1, 0.224% (wb), 5.41 and 25.0% for jackfruit pulp, whereas for mango pulp, the contents are 80.1%, 0.45%, 1.2%, 0.70%, 24.2 mg 100 g−1, 0.48% (wb), 3.79 and 18.0%, respectively. During mechanical drying, it was found that the drying rate decreased with the increase in thickness and for fresh jackfruit and mango pulp, values of index ‘n’ were 0.38 and 0.20 at 60 °C respectively, whereas for steam blanched jackfruit and mango pulp, value of index ‘n’ were 0.38 and 0.29 at 60 °C respectively and these were lower than 2 as predicted by the Fick’s 2nd law of diffusion. The activation energy (Ea) was calculated as 3.12 Kcal g.mole, 2.786 Kcal g-mole−1, 2.90 Kcal g-mole−1 and 2.786 Kcal g-mole−1 for the fresh jackfruit, fresh mango, steam blanched jackfruit and steam blanched mango pulps, respectively. The organoleptic taste test showed that sample 401 (Fruit pulp with sugar and KMS) secured highest score.